PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK INTERAKTIF (E-LKPD) BERBASIS BUDAYA RIAU UNTUK KETERAMPILAN MENULIS TEKS ARGUMENTASI DI SEKOLAH DASAR - Wardani, Citra Yulia; Mulyani, Eva Astuti; Permana, Dede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an Interactive Culture-Based Electronic Student Worksheet (E-LKPD) for Riau to improve argumentative writing skills in elementary schools. The research used the Research and Development (R&D) method with the 4-D model (Define, Design, Development, Disseminate). The results showed that the interactive E-LKPD developed was highly valid with an average score of 96.24% and was very practical for use by teachers (93.64%) and students (87.8%). This E-LKPD is also able to increase learning motivation, understanding of argumentative text structure, and critical and creative thinking skills. The integration of Riau culture, which includes traditional houses and Malay ornaments, makes learning more contextual, meaningful, and brings students closer to real experiences. Additionally, the E-LKPD serves as a medium for preserving local culture while supporting the implementation of the Merdeka Curriculum. Therefore, the interactive E-LKPD based on Riau culture is recommended as an innovative learning medium alternative that supports active and independent learning in teaching argumentative text writing at the elementary school level.